Fused Deposition Modeling 3D Printing: Test Platforms for Evaluating Post-Fabrication Chemical Modifications and In-Vitro Biological Properties - Petra Arany; Eszter Róka; Laurent Mollet; Anthony W. Coleman; Florent Perret; Beomjoon Kim; Renátó Kovács; Adrienn Kazsoki; Romána Zelkó; Rudolf Gesztelyi; Zoltán Ujhelyi; Pálma Fehér; et al. (MDPI AG, 2019)
3D printing is attracting considerable interest for its capacity to produce prototypes and small production runs rapidly. Fused deposit modeling (FDM) was used to produce polyvalent test plates for investigation of the physical, chemical, and in-vitro biological properties of printed materials. The polyvalent test plates (PVTPs) are poly-lactic acid cylinders, 14 mm in diameter and 3 mm in height. The polymer ester backbone was surface modified by a series of ramified and linear oligoamines to increase its hydrophilicity and introduce a positive charge. The chemical modification was verified by FT-IR spectroscopy, showing the introduction of amide and amine functions, and contact angle measurements confirmed increased hydrophilicity. Morphology studies (SEM, optical microscopy) indicated that the modification of PVTP possessed a planar morphology with small pits. Positron annihilation lifetime spectroscopy demonstrated that the polymeric free volume decreased on modification. An MTT-based prolonged cytotoxicity test using Caco-2 cells showed that the PVTPs are non-toxic at the cellular level. The presence of surface oligoamines on the PVTPs reduced biofilm formation by Candida albicans SC5314 significantly. The results demonstrate that 3D printed objects may be modified at their surface by a simple amidation reaction, resulting in a reduced propensity for biofilm colonization and cellular toxicity.